Indwelling double pigtail ureteral stent combined or not with surgery for feline ureterolithiasis: complications and outcome in 15 cases. Issue 8 (August 2014) - Manassero, Mathieu; Decambron, Adeline; Viateau, Véronique; Bedu, Anne-Sophie; Vallefuoco, Rosario; Benchekroun, Ghita; Moissonnier, Pierre; Maurey, Christelle
Ureteral obstruction secondary to ureterolithiasis in cats is a challenging situation. Ureteral stenting has recently been introduced to prevent complications that often occurred after ureterotomy or other invasive surgeries. The purpose of this study is to describe the stenting technique and perioperative difficulties, as well as long-term outcome and complications with ureteral stenting in 12 cats with ureteroliths. Fifteen 2.5 Fr soft double pigtail multi-fenestrated ureteral stents were placed in an anterograde fashion under open surgical approaches and with fluoroscopic guidance in 12 cats. Nine cats received a unilateral stent and three received bilateral stents. Ureterotomy or ureteral resection and end-to-end anastomosis were performed in three and four cases, respectively. In six cats, papillotomy was performed to facilitate dilatator and stent placement. All cats recovered well from the surgical procedure, except one cat, which died during the anaesthesia recovery period. Postoperative complications included dysuria (three cases, diagnosed at 15 days, 1 month and 3 months, respectively), urinary tract infection (one case, 1 month after surgery), stent migration requiring stent replacement (one case, 19 months after surgery) and stent obstruction requiring stent removal (three cases with previously end-to-end anastomosis between 2 and 8 months after surgery). Nine cats (75%) were alive at a mean follow-up of 453 ± 194 (123–720) days. The median survival time was >415 days. Stent placement appeared to be a valuable and safe option for treating ureteral obstruction in cats. However, periodic and long-term monitoring of stents is warranted.